Excitonic Effects in Fe/As K‐Edge Absorption for Iron Based Superconductors: A Combined DFT and BSE Analysis. Issue 3 (20th January 2022) - Ghosh, Soumyadeep; Ghosh, Haranath
Abstract: This work provides a detailed theoretical calculations of Fe/As K ‐edge X‐ray absorption spectra of six different iron based superconducting compounds FeSe, LiFeAs, NaFeAs, KFe 2 As 2 $\text{KFe}_2\text{As}_2$, CaKFe 4 As 4 $\text{CaKFe}_4\text{As}_4$, and KCa 2 Fe 4 As 4 F 2 $\text{KCa}_2\text{Fe}_4\text{As}_4\text{F}_2$, by using three distinct levels of calculations to evaluate the electron–hole interaction properly. First, density functional theory (DFT) in absence of core–hole effect which completely neglects the electron–hole interaction; second, supercell based core–hole calculations where the static electron–hole Coulomb interaction is taken into account; and finally, by solving the Bethe–Salpeter equation (BSE) which takes care of the dynamical screening of photo‐electron and core–hole. The characteristic peaked features and spectral weight distribution in Fe K ‐edge absorption spectrum matches well in both the theoretical methods, especially when "core–hole" effect are explicitly considered for iron chalcogenides. Hence, the electron–hole screening effect is almost equivalent in both the methods for these compounds. Occurrence of an additional higher energy peak and bifurcation of some peaks in the BSE spectrum may be attributed to excitonic effects. BSE based As K ‐edge absorption spectrum differs significantly with the DFT ones in some of the studied compounds, indicating more paramount excitonic effects for As edges. Nonresonant inelastic X‐ray scattering is also investigated at various momentum transfers and converges to corresponding X‐ray absorption spectrum at low momentum transfers. Abstract : This work provides a detailed theoretical calculations of Fe/As K‐edge X‐ray absorption spectra of FeSe, LiFeAs, NaFeAs, KFe2As2, CaKFe4As4, and KCa2Fe4As4F2 compounds using DFT and BSE techniques. The electron‐hole screening effect is almost equivalent in both the methods and occurrence of an additional higher energy peak in the BSE spectrum may found to be attributed as excitonic effects.